A Review of Distribution of Atherosclerosis in the Lower Limb Arteries of Patients With Diabetes Mellitus and Peripheral Vascular Disease. (October 2018) - Lowry, Danielle; Saeed, Mujahid; Narendran, Parth; Tiwari, Alok
Objective: There is a generally accepted hypothesis that patients with diabetes mellitus (DM) have a higher burden of atherosclerotic disease below the knee compared to patients without DM (NDM). The aim of this review was to summarize the evidence regarding this hypothesis. Methods: The literature was searched for papers that compared the anatomical distribution of atherosclerotic disease in patients with DM and those without using radiological imaging. Search terms used included "diabetes mellitus, " "peripheral vascular disease, " "distribution of disease, " "angiography, " "computed tomography angiography, " and "magnetic resonance angiography." Where possible, the number of patients with disease in each arterial segment was extracted and included in a forest plot. A descriptive approach was taken when this was not possible or a scoring system was used. Results: Fourteen studies were included in the review and it was possible to summarize data from 9 of these in a forest plot. Fifteen different arterial segments were described; however, the most commonly used segments that differentiated between proximal and distal disease were aortoiliac (A-I; DM = 466 patients, NDM = 458), femoropopliteal (F-P; DM = 568, NDM = 585), tibial (DM = 306, NDM = 417). The resulting forest plot showed that those with DM were significantly less likely to have disease in the A-I segment (odds ratio [OR]: 0.25 [0.15-0.42]) and significantly more likely to have disease in the tibial segment (OR 1.94 [1.27-2.96]). In the DM group, there was a trend toward relative sparing in the F-P segment, but this does not reach significance (0.66 [0.33-1.31]). Conclusions: These results support the hypothesis that patients with DM are more likely to have atherosclerotic disease in the tibial vessels than NDM. There is however limited information on how individual vessels are affected. Further information on this and a greater understanding of why the distal vessels are more affected are avenues for future research.